Translation and Adaptation of the Indonesian Version of the Maternal Infant Responsiveness Instrument (MIRI) - Astuti, Dyah Dwi; Wanda, Dessie; Utari, Diah Mulyawati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: The interaction between mothers and premature babies in the early period of oral feeding is beneficial for forming social, cognitive, and emotional development. It is essential to assess maternal interactions with premature babies using valid and reliable instruments. However, culturally adapted tools in the Indonesian context remain limited, making localized validation efforts crucial. This research was to analyze the translation and adaptation process of the Indonesian version of MIRI.Methods: The translation and adaptation process followed standard procedures, including forward translation, expert panel review, back translation, pilot testing, and finalization of the instrument. The process involved collaboration with the International Language Institute and experts in pediatric nursing, neonatology, and nutrition. A pilot test was conducted with 30 mothers of premature infants who were receiving care in a neonatal intensive care unit. The evaluation focuses on content validity and reliability of the translation instruments.Results: The translation and adaptation results showed I-CVI between 0.67 to 1.00. The MIRI S-CVI results for all items were 0.91 in the excellent category. The reliability test on mothers showed a Cronbach's Alpha value of 0.74 in the valid and reliable category. Items with lower I-CVI scores were reviewed and refined based on expert feedback to enhance clarity and cultural relevance. Furthermore, participants reported that the questionnaire items were clear and relevant to their experiences during oral feeding interactions with their premature infants.Conclusions: The Indonesian version of the MIRI demonstrates strong validity and reliability for assessing maternal interaction with premature infants during oral feeding. The instrument can be effectively utilized in both research settings and clinical practice, particularly in neonatal intensive care environments where understanding maternal-infant interaction is crucial for supporting early developmental outcomes.